Papan Landfill Leachate Treatment using a Sequencing Batch Reactor and Coagulation - Yong, Zi Jun (2017)
Landfill leachate generation has been increasing dramatically over the past few decades due to the increase of solid waste or municipal solid waste (MSW) as global development continues and people having higher standard of living lead to more material consumption and production of waste. There were many cases in which the treatment of leachate and domestic wastewater involve a two-stage treatment process. Both the sequencing batch reactor (SBR) and coagulation are well-known biological and physiochemical methods which has high efficiency in treating domestic wastewater and landfill leachate for the past few decades. The Papan Landfill in Perak currently has no proper leachate treatment system, therefore SBR will be investigated to treat the Papan landfill leachate. The needs of post treatment after the primary treatment by SBR is a new trend of two-stage treatment technique employed which can greatly improve the treatment effectiveness. The optimum aeration rate, L/min of the SBR, optimal pH and dosage (g/L) of Aluminium Sulphate (ALUM) for coagulation as post-treatment of Papan landfill leachate had been investigated to compare the treatment efficiency of the treated effluent by SBR and after post treatment by ALUM. Firstly, the two-step sequential treatment by SBR followed by coagulation using ALUM had achieved a removal efficiency of 71.03 %, 87.24 %, 91.82 % and 85.59 % for COD, NH3-N, TSS and colour respectively. Moreover, the two-stage treatment process achieved removal efficiency of heavy metals for Cadmium at 95.00 %, Lead at 95.09 %, Copper at 95.39 %, Selenium at 100.00 % removal and Barium at 87.27 %. Hence, the two-step sequential treatment in this research is an effective treatment method for Papan landfill leachate.